TGFB1 rs1800470 Polymorphism is Associated with Circulating TGF-β1 Levels and Left Ventricular Geometry in Hypertensive Patients - Hendri Susilo; Daphne Cheryl Marvella; Lala Mila Avinda; Citrawati Dyah Kencono Wungu; Limperis Kaldis; Rafail C. Christodoulou; Elena E. Solomou; Platon S. Papageorgiou (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Transforming growth factor β1 (TGF-β1) is a major mediator of myocardial fibrosis and cardiac remodeling in hypertension. TGFB1 (rs1800470) and MTHFR (rs1801133) are known for their roles in TGF-β1 regulation and cardiovascular remodeling, with MTHFR rs1801133 potentially influencing TGF-β1–mediated fibrosis through homocysteine metabolism. However, genetic determinants and relationship of these polymorphism with left ventricular (LV) structure remain unclear in the Indonesian population. Clarifying these associations may improve risk stratification and precision care. Therefore, this study was conducted to assess the associations of these polymorphisms and TGF-β1 levels with LV remodeling in essential hypertension.METHODS: Sixty-four adults subjects with essential hypertension were included in this cross-sectional study, and their blood samples were taken. Genotyping of the MTHFR and TGFB1 genes was performed using polymerase chain reaction (PCR), followed by sequencing. Serum TGF-β1 was measured by enzyme-linked immunosorbent assay (ELISA), while LV mass index (LVMI) and relative wall thickness (RWT) were assessed by echocardiography.RESULTS: TGFB1 rs1800470 was significantly associated with higher TGF-β1 levels (p=0.013). In the recessive model, TT homozygotes had higher TGF-β1 than CC+CT carriers (β=1.444; standardized β=0.353; p=0.004). TGF-β1 correlated with LDL cholesterol and diastolic blood pressure (r=0.302; p=0.015 and r=0.277; p=0.027). The TT genotype was associated with higher RWT under recessive and overdominant models (p=0.021 and p=0.028).CONCLUSION: TGFB1 rs1800470 is associated with circulating TGF-β1 concentrations in essential hypertension, suggesting a potential role in hypertensive cardiac remodeling.KEYWORDS: hypertension, TGFB1 polymorphism, TGF-β1, cardiac remodeling, left ventricular geometry, myocardial fibrosis